Synthesis, Characterization, and Handling of EuII-Containing Complexes for Molecular Imaging Applications - Basal, Lina A.; Allen, Matthew J. (Frontiers in Chemistry, 2018)
Considerable research effort has focused on the in vivo use of responsive imaging probes that change imaging properties upon reacting with oxygen because hypoxia is relevant to diagnosing, treating, and monitoring diseases. One promising class of compounds for oxygen-responsive imaging is Eu(II)-containing complexes because the Eu(II/III) redox couple enables imaging with multiple modalities including magnetic resonance and photoacoustic imaging. The use of Eu(II) requires care in handling to avoid unintended oxidation during synthesis and characterization. This review describes recent advances in the field of imaging agents based on discrete Eu(II)-containing complexes with specific focus on the synthesis, characterization, and handling of aqueous Eu(II)-containing complexes.